6(2p-1)2-54=0

Simple and best practice solution for 6(2p-1)2-54=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2p-1)2-54=0 equation:


Simplifying
6(2p + -1) * 2 + -54 = 0

Reorder the terms:
6(-1 + 2p) * 2 + -54 = 0

Reorder the terms for easier multiplication:
6 * 2(-1 + 2p) + -54 = 0

Multiply 6 * 2
12(-1 + 2p) + -54 = 0
(-1 * 12 + 2p * 12) + -54 = 0
(-12 + 24p) + -54 = 0

Reorder the terms:
-12 + -54 + 24p = 0

Combine like terms: -12 + -54 = -66
-66 + 24p = 0

Solving
-66 + 24p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '66' to each side of the equation.
-66 + 66 + 24p = 0 + 66

Combine like terms: -66 + 66 = 0
0 + 24p = 0 + 66
24p = 0 + 66

Combine like terms: 0 + 66 = 66
24p = 66

Divide each side by '24'.
p = 2.75

Simplifying
p = 2.75

See similar equations:

| -3=-n | | 4g+3(-6+3g)=1-g | | p-42=-42 | | -7x-2=-5x+6 | | (x^2+25)(x^2-9)=0 | | -4(-C-16)=-4-16 | | 0=t*lnt | | C=0.5x+22.4 | | 9y-5=23+2y | | 8(x+3)=38 | | 0.5x+9=-4 | | 9p-19=-61+2p | | x^2=-3x+9x | | 2(x-7)+3-5x=23 | | -3+p/6=-5 | | -6.9x+23.3831=-1.1(x-4.237) | | (-2+-2y)+3y=-4 | | 4+11x=7x-1 | | 7x+23x-5=6(5x+8) | | 10x-9=-11 | | 936-(x+24)=72 | | 4x-4+2y=0 | | (9-r)3-12r=33 | | 2(4s+5)-4s=2(2s+4)-9 | | 100y+20x+100= | | 3(x-5)=5(x+5) | | C=0.5x+8x+4000 | | -j+-13j= | | 7-7n+5n=16-55 | | x+(-19)=31 | | (7x+5)+(4x+2)= | | 4(2y-2)=24 |

Equations solver categories